Assessing burden of central line–associated bloodstream infections present on hospital admission - Leeman, Hannah (Am J Infect Control, 2019)
Few data exist on the incidence of central line–associated bloodstream infection present on hospital admission (CLABSI-POA), although the practice of patients maintaining central lines outside of hospitals is increasing. We describe patients presenting to an academic medical center with CLABSI-POA over 1 year. Of the 130 admissions, half presented from home infusion (47%), followed by oncology clinic (22%), hemodialysis (14%), and skilled nursing facility (8%). Efforts to reduce CLABSIs should address patients across the entire health care system.